Trudna historia. Dzieje kresowej rodziny w latach 1898–1957 - Józków, Beata (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
The publication presents the history of the Jodel and Pietkowski families from Odelsk (today in Belarus), whose story begins with the birth of Antoni in 1898. This article constitutes the pleasure of discovering the fortunes of the family based on interviews, reminiscences of the members of the family living in the 30s of the previous century, during the period of occupation and in the post-war times. The invaluable knowledge possessed by Adela Pietkowska, Alfreda Wojdyło, Maria Mularczyk, Anna Kopiec helped to write down the stories of these families and to perpetuate the memory of Kresy Wschodnie (East Borderlands). It was a must – to discover, listen to and tell the impermanent history. Paolo Coelho said that “The story of one person is the story of all of humanity”. This article presents the knowledge of the roots and identity of the family, describes biographies, activities and achievements of the Odelsk inhabitants against the background of the history of Poland, so that the memory of them would not disappear.